SCIENCE, ART AND EDUCATION – THE NEW PARADIGM - Slaus, Ivo (European Scientific Journal, ESJ, 2015)
Contemporary world is global, interdependent, rapidly changing generating uncertainties compounded by bankrupting nature, destroying human and social capitals. In addition, some sovereign countries possess weapons of mass destruction. It is obvious that the current world is not sustainable, and reduction of threats cannot be achieved within the current paradigm. A new social, economic and political paradigm is required and that can be achieved not by violence, but by more knowledge. Power has shifted from military force to wealth and now to knowledge. Power shift does not merely transfer power, it transforms it. New paradigm is a continuous change, where scientific research, art and education play a dominant role.